Solid-state nuclear magnetic resonance studies of hydrogen storage materials - Martin, Gregory Stephen Bernard (2014)
Currently, solid-state nuclear magnetic resonance (NMR) methodology is still evolving. However, this thesis focuses on the application of NMR methods to improving the understanding of solid-state hydrogen storage materials. In particular, this thesis demonstrates how NMR can provide a unique perspective on materials from a molecular level, complementary to other analytical techniques. All of this work has been done in collaboration with other research groups, so effort has been made to interpret the NMR results recorded here in the context of the synthetic methods used and results obtained from other analytical techniques. Firstly, chapter 1 contains a review on the necessity and challenges of storing hydrogen. Then a complete review of the relevant NMR theory and methodology will be given in chapter 2, before turning attention to its application to specific hydrogen storage systems in subsequent chapters. Chapter 3 studies the metal organic frameworks (MOF): NOTT-207, NOTT-201 and NOTT-209 as potential storage systems. Static 7Li studies elucidated the change in the lithium co-ordination environment upon desolvation, necessarily unblocking the pores for gas sorption. Chapter 4 contains a multi-nuclear study on the LiBH4/MgH2 system. In the first part, static 7Li NMR reveals the effects of ball milling (particle grain size reduction) on lithium ion diffusion; for the hexagonal (high temperature) structure of LiBH4. Evidence is also found for significant lithium ion diffusion in the orthorhombic (low temperature) structure. Then in the second part of chapter 4, 1H, 6Li, 7Li, 11B and 25Mg ex situ magic angle spinning experiments were used to follow the route of decomposition, analysing the effects of varying reaction temperature, pressure and sample stoichiometry. The different phases present at different stages in the amorphous intermediates and products were elucidated, in particular it was possible to show the necessary thermodynamic conditions for the [B12H12]2-intermediate formation. Chapter 5 uses static 7Li NMR to study the Li-N-H system. Firstly, Li3N nanowires are characterised in terms of lithium ion diffusion, with an improvement to diffusion being found upon nano-structuring. Then bulk Li2NH and dual phase Li2NH/LiNH2 are also characterised with respect to lithium ion diffusion, and analysis suggests hopping occurs between tetrahedral sites. Since the three systems studied in this thesis are different, each chapter will contain all the background scientfic information and conclusions relevant to the NMR results of the system under consideration. Finally, chapter 6 will summarise and conclude as a whole in the context of the technological importance of this work.